Comparison of Culture, Cytotoxin Assay and Two Eia Tests with Clinical Diagnosis of Clostridium difficile-Associated Diarrhea - Marilyn Binning; Michael A John; Berend C Schieven; Thomas W Austin; Robert Lannigan; Zafar Hussain (Canadian Journal of Infectious Diseases)
Objective: The most common etiology of infectious diarrhea in hospitalized patients is Clostridium difficile. No single laboratory test yields a definitive diagnosis. Four methods were evaluated for their sensitivity and specificity in patients who had clinically defined C difficile-associated diarrhea.